2014
DOI: 10.4161/auto.28678
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy plays an important role in the containment of HIV-1 in nonprogressor-infected patients

Abstract: Recent in vitro studies have suggested that autophagy may play a role in both HIV-1 replication and disease progression. In this study we investigated whether autophagy protects the small proportion of HIV-1 infected individuals who remain clinically stable for years in the absence of antiretroviral therapy, these named long-term nonprogressors (LTNP) and elite controllers (EC). We found that peripheral blood mononuclear cells (PBMC) of the HIV-1 controllers present a significantly higher amount of autophagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 52 publications
1
78
0
Order By: Relevance
“…Further highlighting autophagy in the control of HIV, a recent study found that peripheral blood mononuclear cells from elite controllers contain significantly more autophagic vesicles and express more autophagic markers than normal progressors. Moreover, the same peripheral blood mononuclear cells from elite controllers were more responsive to sirolimus treatment leading to an enhanced autophagic response and a greater reduction in virus production (58). Dissecting the molecular mechanisms by which HIV utilizes autophagy has the potential to lead to the identification of novel drug candidates to treat HIV infection and related opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Further highlighting autophagy in the control of HIV, a recent study found that peripheral blood mononuclear cells from elite controllers contain significantly more autophagic vesicles and express more autophagic markers than normal progressors. Moreover, the same peripheral blood mononuclear cells from elite controllers were more responsive to sirolimus treatment leading to an enhanced autophagic response and a greater reduction in virus production (58). Dissecting the molecular mechanisms by which HIV utilizes autophagy has the potential to lead to the identification of novel drug candidates to treat HIV infection and related opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…(Sagnier et al, 2014) In CD4+ T lymphocytes, autophagy selectively degrades HIV Tat protein, restricting viral replication. (Nardacci et al, 2014) However, it has also been shown that knockdown of autophagy factors in T-cell lines can inhibit HIV replication. (Eekels et al, 2012) Certainly there is a complex relationship between HIV and autophagy, and the nature of the interactions between virus and pathway depend on the cell and the circumstances.…”
Section: The Complex Relationship Between Hiv and Autophagymentioning
confidence: 99%
“…Recently, augmented expression levels of Ambra1 have been found in the peripheral blood mononuclear cells (PBMCs) and lymph nodes of nonprogressor human immunodeficiency virus-1 (HIV-1)-infected individuals, where it contributes to maintaining a robust autophagic response. The sustained autophagy in these individuals is most likely to be responsible for the clinical stability that has been observed in the absence of therapy (Nardacci et al, 2014).…”
Section: Ambra1 and Pathologiesmentioning
confidence: 99%